Spiritual Attitude in the Context of Physics Learning: A Quantitative Review of Class XI Thermodynamics - Firahmi, Muhammad Wildi; Zainuddin, Zainuddin; Haryandi, Surya; Dewantara, Dewi (Universitas Lambung Mangkurat, 2025)
This study aims to determine the achievement of students' spiritual attitudes in developing electronic teaching materials on thermodynamics with Al-Qur'anic verses. The type of research used is development research with students at one of the Islamic-based schools in Banjarmasin class XI in the 2023/2024 academic year. The research instrument used is the spiritual attitude observation sheet instrument. The research data were analyzed using descriptive statistics. The results showed that using electronic teaching materials on thermodynamics with Al-Qur'an verses improved spiritual attitudes from a value of 2.14 to 3.14 with a good category. Using teaching materials for thermodynamics with Al-Qur'an verses can improve the spiritual attitude of students, with details of 1 out of 29 students getting a very good category spiritual attitude score. 21 out of 29 students showed good category spiritual attitudes. 7 out of 29 students showed a fairly good spiritual attitude. The final achievement of students' spiritual attitudes of 3.14 in the good category was declared good based on the results of the observation sheet of students' spiritual attitudes.